Descriptive Study of Maternal Mortality Based On Maternal Characteristic in Semarang City - Hasibuan, Indah Doanita (Jurnal Ilmu Kesehatan, 2024)
Abstract: Maternal mortality in Semarang District was in the 2th ranking (highest) of 35 districts/cities in Central Java Province by 2015. The purpose of this study was to analyze maternal mortality based on maternal characteristics in Semarang City. This research used descriptive analysis, derived from secondary data that taken from Maternal Verbal Autopsy data on maternal death at Semarang City Health Office. The sampling of this study were all death maternal cases whose died during pregnancy, delivery and postpartum in District Semarang as many as 35 people in 2015. From the analysis showed that maternal mortality in Semarang City based on mothers were aged 20-35 years (68.6%), level education in senior high school (54.3%), in working mothers (51.4%), at risk spacing births (52.4%), risk parity (51.4%), place of delivery were 89.2% in hospital, delivery by cesarian section (67.9%). Beside that, most of mortality cases occurred in postpartum period (80%), with the highest caused preeclampsia/ eclampsia (37%) and 71.4% of mothers also do Antenatal Care more than 4 times during pregnancy. There are Most of mothers have a history of heart disease (22.8%), 39.3% preeclampsia/ eclampsia as a delivery complication and 74% mothers with postpartum complication. This study recommends the need for early recognition of mothers about antenatal care and danger during pregnancy, childbirth and postpartum period and increased alertness of health workers to complications of pregnancy, complication of delivery and complication of postpartum especially in mothers with a history of illness.